Statistical Evaluation of Titrimetric Method Using N-Bromosuccinimide (Nbs) and Cyclic Voltammetry for the Assessment of Ascorbic Acid Level in Vegetables and Tuber Products - Azeez, L.A. (International Journal of Pharmaceutical & Biological Archive, 2010)
Titrimetric using N-bromosuccinimide and cyclic voltammetric methods were used to determine the concentration of ascorbic acid in green amaranth (Amaranth candatus) and irish potato (Ipomoea batata). The results were statistically evaluated using F-test for comparison of precision and t-test for evidence of significant difference. Green amaranth showed comparable precision at 1 % confidence level and no significant difference was found between the means of the two analytical methods at 10 %, 5 % and 1 % confidence levels while irish potato showed comparable precision at both 5 % and 1 % confidence levels, significant difference was found for the means of both methods at all confidence levels. The t-test has shown that cyclic voltammetry produced a better and reliable result for tuber products.